A cohort study of differences in trauma outcomes between females and males at four Indian Urban Trauma Centers. Issue 9 (September 2022) - Pendleton, Anna Alaska; Sarang, Bhakti; Mohan, Monali; Raykar, Nakul; Wärnberg, Martin Gerdin; Khajanchi, Monty; Dharap, Satish; Fitzgerald, Mark; Sharma, Naveen; Soni, Kapil Dev; O'Reilly, Gerard; Bhandarkar, Prashant; et al.
Highlights: This study was one of the first of its kind to evaluate sex-based differences in Indian trauma patients across multiple institutions. This multicentre study of outcomes in Indian trauma patients did not demonstrate a significant difference in the 30-day trauma mortality or 24-hour trauma mortality between female and male trauma patients on adjusted analyses. However, subgroup and multivariable analysis provide insight into possible reasons for the inconsistent association between sex and mortality demonstrated in the literature. On multivariable regression, sex was not associated with 30-day mortality or 24-hour mortality. Future research should assess the interplay of injury burden, hormonal/immunological alterations, and gender disparities in trauma patients. Abstract: Background Studies from high income countries suggest improved survival for females as compared to males following trauma. However, data regarding differences in trauma outcomes between females and males is severely lacking from low- and middle-income countries. The objective of this study was to determine the association between sex and clinical outcomes amongst Indian trauma patients using the Australia-India Trauma Systems Collaboration database. Methods A prospective multicentre cohort study was performed across four urban public hospitals in India April 2016 through February 2018. Bivariate analyses compared admission physiological parameters and mechanism of injury. Logistic regression assessed association of sex with the primary outcomes of 30-day and 24-hour in-hospital mortality. Secondary outcomes included ICU admission, ICU length of stay, ventilator requirement, and time on a ventilator. Results Of 8, 605 patients, 1, 574 (18.3%) were females. The most common mechanism of injury was falls for females (52.0%) and road traffic injury for males (49.5%). On unadjusted analysis, there was no difference in 30-day in-hospital mortality between females (11.6%) and males (12.6%, p = 0.323). However, females demonstrated a lower mortality at 24-hours (1.1% vs males 2.1%, p = 0.011) on unadjusted analysis. Females were also less likely to require a ventilator (17.3% vs 21.0% males, p = 0.001) or ICU admission (34.4% vs 37.5%, p = 0.028). Stratification by age or by ISS demonstrated no difference in 30-day in-hospital mortality for males vs females across age and ISS categories. On multivariable regression analysis, sex was not associated significantly with 30-day or 24-hour in-hospital mortality. Conclusion This study did not demonstrate a significant difference in the 30-day trauma mortality or 24-hour trauma mortality between female and male trauma patients in India on adjusted analyses. A more granular data is needed to understand the interplay of injury severity, immediate post-traumatic hormonal and immunological alterations, and the impact of gender-based disparities in acute care settings.